The rising burden of female cancer in Ethiopia (2000–2021) and projections to 2040: Insights from the global burden of disease study - Molalign Aligaz Adisu; Tesfaye Engdaw Habtie; Tegene Atamenta Kitaw; Abraham Dessie Gessesse; Bogale Molla Woreta; Yabibal Asfaw Derso; Alemu Birara Zemariam (PLoS ONE, 2025)
Background Female cancers—breast, cervical, ovarian, and uterine—pose significant public health and socio-economic challenges, particularly in low- and middle-income countries like Ethiopia. However, detailed and geographically disaggregated data are limited, hindering effective policymaking. To address this gap, our study utilizes the Global Burden of Disease (GBD) methodology to analyze 21 years (2000–2021) of national and sub-national trends and risk factors for these cancers in Ethiopia, with projections to 2040, to support targeted cancer control and health system strengthening. Methods Using the 2021GBD data, we analyzed the national and sub-national prevalence, incidence, mortality, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) for female specific cancer in Ethiopia. An Autoregressive Integrated Moving Average (ARIMA) model was employed for projecting epidemiological trajectories through 2040. All statistical analyses and data visualization were performed using Python. Results In 2021, the Ethiopian incidence of female breast, cervical, ovarian, and uterine cancer was 7,308 (95% uncertainty interval (UI): 5,794–9,199), 7,884 (95% UI: 5,759–11,765), 2,054 (95% UI: 1,034–2,929), and 669 (95% UI: 422–1,126), respectively. Cervical cancer accounts for the highest number of DALYs, 162,776 (95% UI: 119,900–239,116), followed by breast, ovarian, and uterine cancer at 155,931 (95% UI: 123,015–196,249), 40,430 (95% UI: 19,885–57,414), and 8,882 (95% UI: 5,579–15,240), respectively. Projections to 2040 indicate a continued rise in incidence for all female cancers. Conclusions Breast and ovarian cancers are emerging public health crises in Ethiopia, with significant increases in prevalence, incidence, and DALYs. While the cervical cancer burden is declining, rising YLDs indicate a growing need for long-term care. The projected rise in female cancer incidence calls for urgent, targeted interventions focused on early diagnosis, age-appropriate screening, and improved cancer care services to reduce the adverse impact on Ethiopian women's health.